Dementia-friendly housing charter. Issue 2 (11th June 2018) - Miles, Sara; Pritchard-Wilkes, Vanessa
Abstract : Purpose: The dementia-friendly housing charter was developed by the sector in response to the Prime Minister's challenge on dementia and a need for this resource within the housing sector. The purpose of this paper is to highlight the positive impact the housing sector can have on people living with dementia and identify resources available which the sector can use to support this. Design/methodology/approach: The charter identifies relevant resources and examples of good practice to encourage their integration into all aspects of people, places and processes, the three "pillars" which the charter is built around. To develop the charter, people with dementia were engaged to identify the challenges they face and potential solutions that could be provided. The feedback of people with dementia highlighted the importance of design in housing to ensure it meets an individual's needs as their dementia progresses. This could include adaptations such as sensor lights, plug sockets at arm level, wet rooms and open plan living. The importance of good quality training for staff was also highlighted. Findings: There are a number of areas that were not included in the housing charter. Some were consciously not included, such as care homes, while others such as issues apparent when considering the wider agenda of equality are now being explored and will be incorporated. Originality/value: In the first three months, over 600 copies of the charter were downloaded by a range of organisations including housing with care providers, local authorities and housing associations. An evaluation of the effectiveness of the charter will take place during Autumn 2017 to understand more about the success and limitations of the charter after which amends will be made if required.